ß-Cryptoxanthin from supplements or carotenoid-enhanced maize maintains liver vitamin A in Mongolian gerbils (Meriones unguiculatus) better than or equal to ß-carotene supplements - Davies, Christopher; Jing, Hua; Howe, Julie; Rocheford, Torbert R.; Tanumihardjo, Sherry A. (Cambridge University Press, 2008)
Maize with enhanced provitamin A carotenoids (biofortified), accomplished through conventional plant breeding, maintains vitamin A (VA) status in Mongolian gerbils (Meriones unguiculatus). Two studies in gerbils compared the VA value of β-cryptoxanthin with β-carotene. Study 1 (n 47) examined oil supplements and study 2 (n 46) used maize with enhanced β-cryptoxanthin and β-carotene. After 4 weeks' depletion, seven or six gerbils were killed; remaining gerbils were placed into weight-matched groups of 10. In study 1, daily supplements were cottonseed oil, and 35, 35 or 17·5 nmol VA (retinyl acetate), β-cryptoxanthin or β-carotene, respectively, for 3 weeks. In study 2, one group of gerbils was fed a 50 % biofortified maize diet which contained 2·9 nmol β-cryptoxanthin and 3·2 nmol β-carotene/g feed. Other groups were given equivalent β-carotene or VA supplements based on prior-day intake from the biofortified maize or oil only for 4 weeks. In study 1, liver retinol was higher in the VA (0·74 (sd 0·11) μmol) and β-cryptoxanthin (0·65 (sd 0·10) μmol) groups than in the β-carotene (0·49 (sd 0·13) μmol) and control (0·41 (sd 0·16) μmol) groups (P < 0·05). In study 2, the VA (1·17 (sd 0·19) μmol) and maize (0·71 (sd 0·18) μmol) groups had higher liver retinol than the control (0·42 (sd 0·16) μmol) group (P < 0·05), whereas the β-carotene (0·57 (sd 0·21) μmol) group did not. Bioconversion factors (i.e. 2·74 μg β-cryptoxanthin and 2·4 μg β-carotene equivalents in maize to 1 μg retinol) were lower than the Institute of Medicine values.